Comparative Analysis of Tourism Policies Among ASEAN Member Countries: A Documentary Research Approach - Phob-udom, Phobphison; Zhao, Yan; Chumnanont, Chanoksuda; Yaiyong, Angkana; Chutiphongdech, Thanavutd (Asia Social Issues, 2025)
This research article examines Thailand’s tourism rivals, Singapore, and Malaysia’s tourism policies. Using a qualitative research approach, this study conducted a documentary analysis of gray literature available in the online public domain from 2020 to 2024. The sources included government white papers, tourism strategic planning documents, government tourism agency websites, online media news releases, and official tourism commercials available on social media platforms. This study employed a comparative policy framework, modifying the OECD’s structure in the process. The findings revealed that Thailand, Singapore, and Malaysia have a primary objective of prioritizing sustainable tourism. These three countries have created organizations dedicated to promoting tourism to sell their offerings effectively. Nevertheless, the disparity among these three countries lies in the limitations imposed on tourism resources, which in turn impact the allocation of budgets and implementing tourism plans and programs in each country. The findings and discussion provide valuable strategic insights for the future formulation of tourism policies. This study provides valuable insights from Thailand tourism rivalries’ comparative analysis, which serves as a foundation for tourism-related authorities to design tourism policies and promote tourism growth in Thailand.